Stability of a Switched Linear System - At-Tasneem, Mohd Amin; Sallehuddin, Mohamed Haris; Zulkifli, Mohd Nopiah (Universiti Malaysia Pahang, 2012)
Hybrid systems are dynamic systems that arise out of the interaction of continuous state dynamics and discrete state dynamics. Switched systems, which are a type of hybrid system, have been given much attention by control systems research over the past decade. Problems with the controllability, observability, converseability and stabilizability of switched systems have always been discussed. In this paper, the trend in research regarding the stability of switched systems will be investigated. Then the variety of methods that have been discovered by researchers for stabilizing switched linear systems with arbitrary switching will be discussed in detail.